Digital transformation of UniKL BMI- An enhanced conceptual business model “University of the Future” - Abu Bakar, Zul Fikri; Zai Zani, Muhammad Syahmi; Ajahar, Amirul Hakim; Ahmad Dahlan, Abdul Rahman (Research Publish Journal, 2018)
Digital transformation is the change that associated with the application of the digital technology in all aspects of human lives. The term or concept of “going paperless” as a reference affects both individual businesses and whole parts of society such as government, mass communications, arts, medicine, science and also education. For higher education, as the world nowadays appears to be driven by the disruptive change in the forces of technology, economic, political and education sector which threaten to undermine the business model, governmental support, and operation. Malaysian higher education system must transform in order to survive in an increasingly competitive global economic environment. One of the transformation initiatives is the digital transformation of the Malaysian universities. Hence, the focus of this paper is to digitally transform University of Kuala Lumpur (UniKL). The methodology used is based on COBIT implementation framework, literature review, interview, and business-modelling framework. The main contribution of the paper is a conceptual enhanced business model and game changers specifically for digitally transforming UniKL, and generally can be adapted by other universities.